Transparansi Kebijakan Publik Sebagai Strategi Nasional Dalam Menanggulangi Pandemi Covid-19 - Afni Regita Cahyani Muis (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThe world is confronted with the COVID-19 pandemic which devastated social activities, the economic sector, politics, and even education. Countries that are threatened by the effects of the COVID-19 pandemic are making various efforts to tackle the outbreak of the deadly virus. The concept of government transparency plays a key role in providing effective decision making for public policy outputs in rapid response to COVID-19 response. Transparency Analysis in this research is public policy in various countries, such as China, South Korea, Taiwan, Vietnam, and Canada, which have successfully applied the concept of transparency to realize a system of good governance. This research aims to be lessons from other countries for national strategies, especially Indonesia in tackling the COVID-19 Pandemic. This research method is a comparative study with learning experience as a media analysis with a literature review.Keywords: Transparency, Public Policy, National Strategy, Pandemic, COVID-19 AbstrakDunia sedang diperhadapkan dengan pandemi COVID-19 yang meluluhlantakkan aktivitas sosial, sektor ekonomi, politik, bahkan pendidikan. Negara-negara yang terancam terkena dampak pandemi COVID-19 melakukan berbagai upaya untuk menanggulangi wabah dari virus mematikan tersebut. Konsep transparansi pemerintah memainkan peran kunci dalam memberikan decision making yang efektif bagi output kebijakan publik dalam aksi cepat tanggap penanggulangan COVID-19. Analisis Transparansi dalam penelitian ini adalah kebijakan publik di berbagai negara, seperti Tiongkok, Korea Selatan, Taiwan, Vietnam, dan Kanada yang berhasil menerapkan konsep transparansi untuk mewujudkan sistem good governance. Penelitian ini bertujuan menjadi lessons dari negara lain bagi strategi nasional, khususnya Indonesia dalam menanggulangi Pandemi COVID-19. Metode penelitian ini merupakan studi komparasi dengan learning experience sebagai media analisis dengan kajian literatur. Kata Kunci: Transparansi, Kebijakan Publik, Strategi Nasional, Pandemi, COVID-19